Perancangan Alat Pengering Pada Proses Produksi Kapsul Daun Kelor bagi Kelompok Tani Desa Guntung Manggis - Rachmat Subagyo; Muhammad Nizar Ramadhan; Ma'ruf Ma'ruf; Azie Aprianto; Muhammad Nazief Maulidinnur; Deni Saputra; Annisa Nurul Kharisma; Mutea Putri Dwianto; Devina Yulie Fatria; Siti Rabiatul Adabiah (Universitas Lambung Mangkurat, 2023)
Guntung Manggis Village is one of the sub-districts located in Landasan Ulin District, Banjarbaru City, South Kalimantan Province. Some of the problems in the Guntung Mangosteen subdistrict that were obtained based on the survey results were that the drying process for making moringa leaf capsules was quite time consuming because they could not be dried directly in the sun. And the hygienic and clean drying process for Moringa leaves meets health standards. The method for solving this problem is to design and manufacture a hygienic Moringa leaf dryer. To perfect the manufacture of a Moringa leaf dryer, it is necessary to carry out a simulation first. The simulation results show that a dryer that uses 15 Watt lamp power has a better heating process because the entire heating area is a homogeneous blue color so that the drying process will take place evenly. This drying process is the best where there is no excess temperature at the base of the tool so it does not require a blower to remove heat. The dryer is more efficient because the lamp power is small and does not require a blower to homogenize the temperature of the dryer.